Autoretrato do sonhador: memórias e projetos de vida dos agentes jovens do Bairro Presidente Kennedy - Sacramento, Robério Augusto Leal (2009)
This study aims at understanding the youth and the formation of social representation through biographical reports of the young participants of Projeto Agente Jovem de Desenvolvimento Social e Humano of the residential quarter Presidente Kennedy in Fortaleza, in 2007. The participating of young people in this unformed education policy leads to a job with temporality, putting them in contact with the exercise of evocating their memories and building their life projects. The relation established between memory and their external representations about education, sexuality, work and leisure time have let us to reflect about the role of the school and the family in their lives and the need to undo designed represents on the youth of poorer neighborhoods. We used as resources for such analyses, interviews with young people, texts and drawings produced by them during the activities of the project.